ŞAMANİZM ÜZERİNE BİR ARAŞTIRMA - TUNÇ, ZEKİYE (Fırat Üniveristesi, 2007)
Şamanizm, milattan önceki çağlardan günümüze yaşayan bir inançtır. Kökeni Orta veKuzey Asya'ya dayandırılan bu oluşum, Kuzey ve Güney Amerika'da Avustralyayerlilerinde, Endonezya'da, Güneydoğu Asya, Çin, Tibet ve Japonya'da da görülmüştür.Şamanizm, kişi-tanrı-ruh arasında iletişimi sağlayan dinsel bir olgu olarak tanımlanır.Yapısında sihri ve mistik öğeleri taşır. Daha çok ruhlarla iletişimi ön plana alan şamanizmdegaye insanların işlerinin düzenli yol almasıdır. Şamanizmde, kişi-tanrı-ruh iletişimi yapan kişişamandır. Şaman aldığı eğitimin verdiği potansiyelle esrime tekniklerini kendisinde depolar.Bu özellik şamanı güçlü kılar ve insanların başvurduğu biri olur. Şaman özelikle ayinleraracılığıyla ruhlarla temasa geçer. Böylelikle ortada insan hayatını olumsuz etkileyendurumları ortadan kaldırır.Şamanizm köken olarak Asya kaynaklıdır. Bu nedenle özellikle Altay kavimlerincebenimsenmiştir. Türklerin, Asya kaynaklı inancı olan şamanizm devlet boyutunda görülmesebile halk boyutunda yaşama alanı bulmuştur. Özelliklede göçebe kesimlerde devam etmiştir.Halkın kötülükler karşısında başvurduğu çeşitli geleneksel korunma yöntemleri şamanizmdenkaynaklanmıştır.Anahtar kelimeler: Şamanizm, Şaman, Ayin, Ruh, Asya, Altay, Türk.

Shamanism is a faith which has been existed from before Christ until today. Thisform of faith, which is depended to Middle and North Asia, was also seen in Australianresidents in Northern and Southern America, Endonesia, South-East Asia, China, Tibet andJapan.Shamanism is defined as a religious act which provides communication betweenIndividual-God-Spirit. It possesses magic and mystic components within its structure. InShamanism, which brings communication especially with spirits, the aim is regular progressof works. In shamanism, the shaman realizes communication between God and spirit. Shamanstores trance techniques within himself thanks to potential provided by training. Thischaracteristic makes shaman powerful and he becomes an individual whom people refer.Shaman contacts with spirits especially through religious ceremonies. Consequently, heeliminates conditions which affect life of people adversely.Origin of Shamanism lies in Asia. Therefore, it was adopted especially by societyresiding around Altai Mountains. Shamanism, which forms Asia-originated faith of Turkishpeople, had found a space to live among community although it can not be encountered ingovernmental level. Several traditional protection methods used by community againstvarious iniquities arised from Shamanism.Key Words: Shamanism, Shaman, Religious Celebration, Spirit, Asia, Altai Mountains,Turk.
A research on the shamanism
Keywords: Din